Systems thinking for social change : a practical guide to solving complex problems, avoiding unintended consequences, and achieving lasting results / David Peter Stroh. - Stroh, David Peter, 1950- (Chelsea Green Publishing, 2015)
By applying conventional thinking to complex social problems, we often perpetuate the very problems we try so hard to solve, but it is possible to think differently and get different results. David Stroh enables readers to contribute more effectively to society by helping them understand what systems thinking is and why it is so important in their work. He also gives concrete guidance on how to incorporate systems thinking in problem solving, decision making and strategic planning without becoming a technical expert, as he walks readers through techniques he has used to help people end homelessness and increase affordable housing, improve public health, strengthen public education and access to early childhood development services, protect child welfare and more.